RANCANGBANGUN RANGKAIAN INVERTER SPWM UNIPOLAR 1 FASA DENGAN PENGATURAN FREKUENSI OUTPUT - Fathoni; Agus Pracoyo; Totok Winarno; Rizal Sabillah (Jurnal Teknik Ilmu dan Aplikasi, 2020)
Changing the dc sgnal to ac signal is done for te purpose of load regulations, such as the ac motor speed, heater and lamp. Inverter work is done by ac rectification first and then converted again to a 1 phase ac signal. The ac output signal is a sinosoidal PWM (SPWM) type of unipolar 220 volts from the input 24 volt dc voltage. Unipolar SPWM signal generation is done by a microcontroller with programming. The number of counts (resolutions) of the SPWM signal and the period are set from the amount in the register, can be set to 8 bits or other constants. The power part of the SPWM inverter is the N channel MOSFET bridge circuit H with IR2110 solid state driver. Step transformer as a load while step-up the inverter output voltage. Determination of the output frequency is set through a rotary encoder that can be adjusted up (increment) or down (decrement). There are 5 frequency variations, namely 30, 40, 50, 60 and 70 Hz. To get the inverter efficiency, the type of MOSFET used is chosen to have the type that has a low RDS (on) value and the right driving pulse, according to the switch configuration. Measurement of the output frequency is done by reading the image on the osciloscope. The observations show a frequency value that is almost the same as the constant. The test results show the difference in output voltage which is reduced at a 30 watt load.